Interface pressure distribution of conventional and 3D-printed sockets using finite element analysis - Zulkiflee, Farisya Farhana (2023)
Prosthetic socket is the main component that requires extra details in designing and fabricating the prosthetic leg in order to ensure the comfortability, stability, and functionality of the amputee while using it. In the advancement of prosthetic socket fabrication, various approaches have been applied to fabricate the socket. In this study, particular attention was given to the measurement of the amputee's stump, which served as the foundation for creating a well-fitting socket. There were two measurement methods were applied which were manual and 3D-printed measurement. Manual measurement involved direct physical measurements taken by a prosthetist, while 3D scanning utilized advanced imaging technology to create a three-dimensional digital representation of the stump, allowing for a more accurate and detailed depiction. The 3D-scanned of mould and actual stump models were imported to the CAD software to develop the 3D geometrical model of the socket. The development of both 3D-printed and conventional models relied on the first objective of this study. Secondly, this study aims to conduct Finite Element Analysis (FEA) in order to observe the interface pressure distribution between stump-socket contact. There were nine points of interest involved in this study. which were patella, patella tendon, tibia end, lateral and medial supracondylars, fibula head, medial middle, popliteal and posterior distal. These points were located on four main regions of the stump, which are anterior, lateral, medial, and posterior. An extensive analysis of the data on interface pressure between stump-socket contact was explained in this study. The coefficient of friction value applied on this contact was 0.7 which indicated that there was a relatively moderate resistance to motion between these two surfaces. There were several distinct conditions applied in FEA such as the amputee's postures which varied in amount of load exerted on the stump. Interface pressure distribution for 3D-printed and conventional sockets in standing and mid-stance posture were analyzed. Overall, some points of interest involved in pressure-tolerant areas recorded high interface pressure between the stump and socket contact for both 3D-printed and conventional sockets, especially on patella tendon. Interface pressure on patella tendon in standing posture exhibited about 36.47 kPa and 33.68 kPa for 3D-printed and conventional sockets respectively. There were several graphs illustrated to present the curve trend of different comparisons. From the findings, there is significant correlation between the interface pressure and amount of load exerted. It resulted in higher interface pressure for each points when higher load was exerted, especially on the pressure-tolerant areas on the stump.